Environment sound technologies: exploring and modelling barriers using modified UTAUT model. (2016) - Singh, Manju; Behl, Abhishek
The world is a competitive arena where survival is dependent on sustainability. Environment has gradually changed and had influenced the sustainable development in the recent past. The changing era of technology has played a vital role in enhancing sustainable development through environmental ecosystem. This paper explores a niche area of environmentally sound technology (EST) to understand the holistic view of sustainable development through the microscope of society in India. This paper aims at exploring the barriers in adoption of EST in rural India and modelling the barriers in a revised unified theory of acceptance and use of technology (UTAUT) model. It also projects revision in the model by adding moderating effect of prior experience, gender and age of end users to understand the change in behavioural intention of the user in rural areas. The results reflect difference in behavioural intention and degree of usage for different age groups and gender. The results derived from primary data collection showcase a classified result of barriers clearly justifying the moderating effect by each of the external factors. The revised UTAUT model is one of the few models knit for EST in a rural dynamics like India.